Paracentesis, puncture lavage of the peritoneum or diagnostic laparotomy in the severely injured - Cazabán, Luis; Chifflet, Juan A. (Cirugía del Uruguay, 1975)
The procedures of paracentesis, peritoneal lavage and diagnostic laparatomy are discussed in the appraisal of the abdominal lesions of patients with severe multiple injuries. The limitations of the former two, with an important percentage of false negatives, may create a false security in the evaluation of the results, which frequently leads to a therapeutic delay, sometimes with deadly consequences. Only the exploratory laparatomy is a safe diagnostic resource and its indicatións are broader and broader in this field of traumatologic surgery.